Virtual reality simulation as a training tool for perfusionists in extracorporeal circulation: Establishing face and content validityCentral MessagePerspective - Zaheer U.D. Babar, BSc, EKP, ECCP; Samuel A. Max, BM, Bch(Oxon); Bryan G. Martina, MD; Rodney A. Rosalia, PhD, MBA; Jette J. Peek, MSc; Antony van Dijk, BSc, EKP; Amir H. Sadeghi, MD, PhD; Edris A.F. Mahtab, MD, PhD (JTCVS Techniques)
Objective: We conducted a prospective study to assess the face and content validity of a new virtual reality (VR) extracorporeal circulation simulator (ECC) developed for perfusionists to facilitate training and practice. We evaluated the opinions of students and staff members about the feasibility of the simulation. The 2 groups consisted of experts (qualified perfusionists) and novices (trainee perfusionists). Methods: Perfusionists (n = 12 experts and n = 11 trainees) received instructions on how to use the VR simulator and then proceeded to perform the start of cardiopulmonary bypass in the VR environment. Participants then completed a Usefulness, Satisfaction, and Ease of Use Questionnaire. The questions were rated on a 5-point Likert scale, ranging from 1 (fully disagree) to 5 (fully agree), to assess the face validity and content validity of this simulator. Results: Participants reported a predominantly positive experience with the VR-ECC simulator, with 96% (n = 22) agreeing that the simulator was a useful way of training ECC scenarios. All participants found it easy to interact with the software (100%, n = 23), and 82% of students (n = 9) believed it helped them remember the steps involved with initiating ECC. Finally, (87% [n = 20]) of participants believed the image quality and depth perception were good. Conclusions: Our next-generation simulator was valid for face and content constructs, and almost all participants found it to be a useful way of training for ECC scenarios. This simulator represents a first step toward truly blended digital learning and a new interactive, flexible, and innovative modality for perfusion training.